Comparative Study of Inflation Trends and Exchange Rate Fluctuations Across Seven ASEAN Member Countries - Amin Hou; Darwin Lie; Nagian Tony (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study investigates the monetary transmission mechanisms influencing inflation and exchange rates across seven Southeast Asian countries (Myanmar, the Philippines, Indonesia, Malaysia, Singapore, Thailand, and Vietnam) over the period 2010–2023, with special focus on the impact of the COVID-19 pandemic. The research addresses the problem of macroeconomic instability, particularly the volatility in inflation and currency values during crisis periods, and aims to identify the dominant monetary factors affecting these indicators. The study employs a mixed quantitative approach using Structural Vector Autoregression (SVAR), Panel Autoregressive Distributed Lag (ARDL), and Paired Sample t-Test to analyze the short-term and long-term relationships among key variables: Gross Domestic Product (GDP), investment, money supply (M2), interest rates, inflation, and exchange rates. Findings reveal that GDP is the most influential factor impacting both inflation and exchange rates, followed by money supply and interest rates. The variance decomposition analysis confirms that these monetary variables significantly explain macroeconomic fluctuations in both pre- and post-pandemic contexts. The t-Test further indicates statistically significant changes in inflation and exchange rates before and after the pandemic, highlighting the disruptive effect of COVID-19 on economic stability. The results demonstrate that inflation declined significantly in most countries during the pandemic, while exchange rate behavior varied depending on economic resilience and policy responsiveness. The study concludes that maintaining macroeconomic stability requires not only monetary policy coordination but also effective public health crisis management. This research contributes to the regional policy discourse by offering empirical insights and evidence-based recommendations to strengthen economic resilience in Southeast Asia.